2021
DOI: 10.1038/s41598-021-99428-0
|View full text |Cite
|
Sign up to set email alerts
|

Nash equilibria in human sensorimotor interactions explained by Q-learning with intrinsic costs

Abstract: The Nash equilibrium concept has previously been shown to be an important tool to understand human sensorimotor interactions, where different actors vie for minimizing their respective effort while engaging in a multi-agent motor task. However, it is not clear how such equilibria are reached. Here, we compare different reinforcement learning models to human behavior engaged in sensorimotor interactions with haptic feedback based on three classic games, including the prisoner’s dilemma, and the symmetric and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Here a question arises of whether learning the action(s)-value and predicting the partner actions occur independently, or are actually part of one single process. In a recent study focusing on sensorimotor versions of classical discrete games, Lindig-León et al (2021) observed that convergence to a Nash equilibrium is consistent with a model-free form of reinforcement learning, in which actions are generated as a trade-off between their value and the requirement of minimizing their change with respect to the previous trial. This learning mechanism does not explicitly account for partner actions, but it is unclear if it would extend to more complex forms of coordination that involve more than just discrete decisions.…”
Section: Learning In Joint Actionmentioning
confidence: 69%
“…Here a question arises of whether learning the action(s)-value and predicting the partner actions occur independently, or are actually part of one single process. In a recent study focusing on sensorimotor versions of classical discrete games, Lindig-León et al (2021) observed that convergence to a Nash equilibrium is consistent with a model-free form of reinforcement learning, in which actions are generated as a trade-off between their value and the requirement of minimizing their change with respect to the previous trial. This learning mechanism does not explicitly account for partner actions, but it is unclear if it would extend to more complex forms of coordination that involve more than just discrete decisions.…”
Section: Learning In Joint Actionmentioning
confidence: 69%
“…In previous studies, it was found that such haptic couplings between two different players in the Prisoner's Dilemma are compatible with the Nash solution, as most interaction endpoints laid in the same quadrant of the workspace than the Nash equilibrium [31]. Similar analyses have also advocated the adequacy of the Nash solution concept for describing sensorimotor interactions in more general scenarios, including mixed equilibrium games like matching pennies [57], coordination games with multiple Nash equilibria like the battle of sexes, chicken or stag hunt [32] as well as Bayesian games that require sensorimotor communication [34]. Importantly, none of the above studies could distinguish the Nash solution from the quantal response equilibrium, as the two solution concepts are often very close together and perfectly coincide in the absence of computational or precision limits.…”
Section: Discussionmentioning
confidence: 80%
“…The corresponding shifts for the response frequencies of player 1 reproduce the same pattern as observed in the human players. This suggests that reinforcement learning models based on Q-learning cannot only explain convergence to Nash equilibrium solutions [57], but more generally convergence to quantal response equilibria.…”
Section: Resultsmentioning
confidence: 99%
“…However, the vast majority of previous studies addressing joint action within a game theoretic framework only focus on equilibrium situations [4,17]. Very few studies [6,19,20] have addressed the way joint coordination is negotiated and learned in scenarios that involve movements. One simple learning strategy when the players play repeatedly the game is that at every round each player determines their best response based on their beliefs about how their opponents will play (fictitious play, FP)see [21,22].…”
Section: Introductionmentioning
confidence: 99%